Gene expression profiling of peripheral blood mononuclear cells in young male trampoline athletes - Gao, L.; Yang, Y. J.; Li, E. Q.; Mao, J. N. (Exercise Biochemistry Review, 2018)
Objective Evidence indicates that physical activity influence bone health. However, the molecular mechanisms mediating the beneficial adaptations to exercise are not well understood. The purpose of this study was to examine the differentially expressed genes in PBMC between athletes and healthy controls, and to analyze the important functional genes and signal pathways that cause increased bone mineral density in athletes, in order to further reveal the molecular mechanisms of exercise promoting bone health.